PENDIDIKAN SEKSUAL PADA REMAJA TENTANG HIV - Suci Fitriana Pramudya Wardani (Jurnal Pengabdian Masyarakat Putri Hijau, 2022)
Human Immunodeficiency Virus (HIV) is a virus that can cause Acquired Immuno Deficiency Syndrome (AIDS). This virus attacks white blood cells and can damage the human immune system. The low knowledge of adolescents about adolescent reproductive health, especially in protecting themselves from risky sexual behavior, preventing unwanted pregnancies and the large number of adolescents who perceive HIV/AIDS as a harmless disease and a lot of misunderstandings related to the disease are very important problems. Efforts to increase knowledge about HIV are carried out by providing health education using the lecture method and pre and post-test evaluation. After the health education activities, students' knowledge of HIV/AIDS was obtained.